An outcome evaluation of a New Zealand farm safety intervention: A historical cohort study. Issue 4 (17th December 2013) - Cryer, Colin; Langley, John D.; Samaranayaka, Ari; Davie, Gabrielle; Morgaine, Kate; Lilley, Rebbecca; Barson, David
<x xml:space="preserve">Abstract</x> Background There is limited evidence that farm safety‐related interventions based solely on an educational element have an effect on injury rates. Our aim was to evaluate a New Zealand national educational program, FarmSafe™ Awareness, for its effect on injury rates. Methods We used a before‐after design followed by a historical cohort study of sheep, beef, and dairy farmers/workers. The outcomes were work‐related injuries, identified from workers compensation data. Cox regressions were used to compare intervention with matched control group rates. Results FarmSafe™ Awareness was associated with significantly higher rates of work‐related injury, than matched controls. Conclusions It is difficult to see how FarmSafe™ Awareness could be causing an increased rate of work‐related injury. We detected no reporting bias, and selection bias is likely to act in the opposite direction to the observed results. We conclude that there is no evidence that FarmSafe™ Awareness prevents farm injury. Am. J. Ind. Med. 57:458–467, 2014. © 2013 Wiley Periodicals, Inc.